Irving S. Friedman. Inflation, a world-wide disaster. Boston, [Mass.] : Houghton Mifflin Co., 1973. 378 p. - Méndez Villarreal, Sofía (Estudios Demográficos y Urbanos, 1973)
IRVING S. FRIEDMAN, Inflation, a World-wide Disaster, Boston, Houghton Mifflin Co., 1973.